Dilema Ex-Officio Terkait Pencegahan Korupsi Dan Penjaminan Mutu Di Perguruan Tinggi Swasta - Suci, Afred; Maryanti, Sri; Van FC, Lucky Lhaura; Yandra, Alexsander (Jurnal Penjaminan Mutu, 2020)
Conflicts of interest are the entry point for the abuse of power and corruption. The implementation of a manipulative ex-officio system that tends to perpetuate the oligarchy will cause a corrupt behavior in the governance of private higher education institutions. To date, studies on ex-officio related to higher education governance have never been discussed academically. The purpose of this study, thus, aims to criticize the application of ex-officio and its potential consequences in the supervision system at private higher education institutions. The study used a qualitative exploratory and the literature study was employed. The result reveals that the ex-officio is a legal model used in many higher education institutions. However, in its application it can lead to conflicts of interest and abuse of power which in turn has the potential of corrupt behavior university governance.